HUBUNGAN ANTARA PENERAPAN STANDART OPERATIONAL PROCEDUR (SOP) PEMBERIAN OBAT PRINSIP ENAM BENAR DENGAN TINGKAT KEPUASAN PASIEN DI RST BHAKTI WIRA TAMTAMA SEMARANG: THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF STANDARD OPERATIONAL PROCEDURES (SOP) FOR THE PROVISION OF DRUG PRINCIPLES OF THE SIX CORRECT PRINCIPLES AND THE LEVEL OF PATIENT SATISFACTION AT RST BHAKTI WIRA TAMTAMA SEMARANG - Suprapti E; Azhari N.K; Lestariningsih (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2020)
Satisfaction is a person's feelings of pleasure or disappointment that arise after comparing the results of a service that are in accordance with or not in accordance with the expectations they had before getting service. Patients as users of nursing services demand nursing services in accordance with their rights, namely quality nursing services. In providing nursing services, Standard Operational Procedure (SOP) is very important to assist nurses in achieving quality nursing care. In giving medicine, one must pay attention to the six